A Review on Synthesis, Functionalization, Processing and Applications of Graphene Based High Performance Polymer Nanocomposites - Hawal, Tushar T.; Patil, Maharudra S.; Swamy, Siddalinga; Kulkarni, Raviraj M. (Current Nanoscience, 2022)
Graphene as a nanofiller has gained tremendous importance in polymer nanocomposites for many applications. The attractive properties of graphene related to mechanical, electrical, and thermal domains pose a lucrative means of reinforcing the polymers to obtain the needed properties. The rise in the use of polymers supports this trend and urge researchers to excavate the hidden plethora of nanocomposite materials for multifunctional applications. In this review, an overview is provided on graphene-based materials which have been used extensively in various fields such as batteries, aerospace, automobile, and biomedical fields. With the increasing trend of graphene usage by many researchers as a nanofiller in polymer composites, its types, processing methods are highlighted with suitable applications to assimilate the updates in the development of graphene nanocomposites.
Keywords: Graphene